2005
DOI: 10.1074/jbc.m411069200
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Reactivity of Human Mitochondrial 2,4-Dienoyl-CoA Reductase

Abstract: Fatty acid catabolism by ␤-oxidation mainly occurs in mitochondria and to a lesser degree in peroxisomes. Polyunsaturated fatty acids are problematic for ␤-oxidation, because the enzymes directly involved are unable to process all the different double bond conformations and combinations that occur naturally. In mammals, three accessory proteins circumvent this problem by catalyzing specific isomerization and reduction reactions. Central to this process is the NADPH-dependent 2,4-dienoyl-CoA reductase. We prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 44 publications
2
38
0
Order By: Relevance
“…As a result, the tyrosine moves by the distance of one complete helical turn along the helix from which it is displayed. In dienoyl-reductases, which catalyze a 1-6 hydrogen addition, the tyrosine residue is moved to a different framework segment altogether (50). Why in 5␤-POR yet another solution for the active site has been adopted when compared with other enoyl-reductases is again not obvious.…”
Section: ) (44)mentioning
confidence: 99%
“…As a result, the tyrosine moves by the distance of one complete helical turn along the helix from which it is displayed. In dienoyl-reductases, which catalyze a 1-6 hydrogen addition, the tyrosine residue is moved to a different framework segment altogether (50). Why in 5␤-POR yet another solution for the active site has been adopted when compared with other enoyl-reductases is again not obvious.…”
Section: ) (44)mentioning
confidence: 99%
“…1C). This is in contrast to the tetramer observed for mDCR packed in the crystal lattice (20). Such a pure (Ͼ95% purity as judged by SDS-PAGE analysis) but heterogeneous pDCR was active against the substrate HXC when tested for activity (Table 2).…”
Section: Resultsmentioning
confidence: 40%
“…An invariant lysine, a tyrosine, a serine, and an asparagine have been shown to participate in reactions catalyzed by enzymes belonging to the SDR superfamily, including mDCR (20). Analysis of the primary amino acid sequence of the pDCR by aligning it with that of its counterpart from mitochondrion revealed that pDCR does not contain two of the four residues important for catalysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations